2017
DOI: 10.1016/j.ssi.2017.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Scalable synthetic method for SOFC compounds

Abstract: A B S T R A C TAlthough economically competitive SOFC systems seems to be ready for commercialization, a broad inventory of key starting materials and fabrication processes are needed to enhance systems and reduce costs. These necessities are raised by the demands for large scale SOFC industrial production. Taking into account these reasons, we have synthesized the mean components of a fuel cell, on a large scale, by the glycine nitrate combustion method.The The obtained materials have been characterized by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…GNP requires a short time to produce big quantities of different compounds for SOFC fabrication 161 . A previous study reported that the process was reproducible, and the different batches have homogenous crystallite sizes with porous structures.…”
Section: Wet Chemical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GNP requires a short time to produce big quantities of different compounds for SOFC fabrication 161 . A previous study reported that the process was reproducible, and the different batches have homogenous crystallite sizes with porous structures.…”
Section: Wet Chemical Methodsmentioning
confidence: 99%
“…• Ability to produce homogenous ceramic/composite powders • Ability to produce high-purity powders • High energy efficiency • Ability to produce ultrafine powders GNP requires a short time to produce big quantities of different compounds for SOFC fabrication. 161 A previous study reported that the process was reproducible, and the different batches have homogenous crystallite sizes with porous structures. In addition, the microstructure and purity were maintained during the process.…”
Section: Conventional Glycine-nitrate Processmentioning
confidence: 98%
“…In the case of LSF and LNF, the resulting powders were pelletized and calcined in air at 950 C for 8 h to obtain pure single phase samples. The properties (composition, morphologies, TEC and conductivities) of the primary materials used in the present study could be consulted in previous works [46].…”
Section: Synthesis and System Fabricationmentioning
confidence: 99%
“…In the past few decades, unquestionable advantage was given to develop technologies for the appropriate industrial production of solid oxide fuel cells (SOFCs) [1,2]. Development of strong and sTab.…”
Section: Introductionmentioning
confidence: 99%
“…Development of strong and sTab. high-temperature structural ceramics for SOFCs is nowadays one of the very interesting research topics [1,2]. In the past few years the research was focused to reduce the operating temperature in the intermediate area (500-700 °C) and formation intermediate temperature solid oxide fuel cells (IT-SOFC) with high energy efficiency [3,4].…”
Section: Introductionmentioning
confidence: 99%